2018
DOI: 10.1002/adom.201700939
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Plasmonic Color Generation Based on Phase Transition of Vanadium Dioxide

Abstract: Plasmonic color filtering and color printing have attracted considerable attention in recent years due to their supreme performance in display and imaging technologies. Although various color‐related devices are designed, so far very few studies have touched the topic of dynamic color generation. In this article, dynamic color generation is demonstrated by integrating plasmonic nanostructures with vanadium dioxide based on its tunable optical properties through insulator–metal transition. Periodic arrays of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(98 citation statements)
references
References 55 publications
2
96
0
Order By: Relevance
“…Kats et al have shown that the mid‐infrared plasmonic response of nanoantenna arrays can be modulated by using the index change of an underlying VO 2 substrate in proximity to its phase transition . Recent studies showed that, via direct thermal control, dynamically manipulated plasmonic color ( Figure a), extinction ratio, and polarization state of light (Figure 3b) can be achieved in hybrid metasurfaces integrated with VO 2 nanostructures.…”
Section: Phase Change Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kats et al have shown that the mid‐infrared plasmonic response of nanoantenna arrays can be modulated by using the index change of an underlying VO 2 substrate in proximity to its phase transition . Recent studies showed that, via direct thermal control, dynamically manipulated plasmonic color ( Figure a), extinction ratio, and polarization state of light (Figure 3b) can be achieved in hybrid metasurfaces integrated with VO 2 nanostructures.…”
Section: Phase Change Materialsmentioning
confidence: 99%
“…a) Temperature dependent plasmonic color observed in arrays of silver nanodisks on VO 2 films. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Phase Change Materialsmentioning
confidence: 99%
“…filter device that realizes multiple channels working simultaneously by changing the number of concentric apertures [11]; A color sensor was realized using interference effects in the metal-insulatormetal Fabry-Perot (FP) cavity of polydimethylsiloxane (PDMS) as the dielectric layer [12]; The function of displaying different colors in the visible light range is realized by changing the material characteristics and the geometric parameters of the structure, in order to achieve the application of the structure color [13][14][15][16][17][18][19]. However, the devices proposed by researchers have the defects of single function, complex structure and expensive materials; they cannot achieve better performance when the devices are integrated.…”
Section: Design and Modelingmentioning
confidence: 99%
“…In recent years, the enhanced optical transmission (EOT) effect brought by metal-based surface plasmons has been applied in different wavelengths, including visible light, near-infrared and infrared ranges. Correspondingly, a large number of micro/nano structures have been proposed, such as: circle holes [4], stripe grating hole [5], single/double aperture hole [6], composite structure [7], cross-shaped hole [8], triangular hole [9]; Also, a large number of devices and applications have been constructed, for example: A absorber device that realizes broadband multifunctional properties by introducing vanadium dioxide into a metamaterial [10]; A filter device that realizes multiple channels working simultaneously by changing the number of concentric apertures [11]; A color sensor was realized using interference effects in the metal-insulator-metal Fabry-Perot (FP) cavity of polydimethylsiloxane (PDMS) as the dielectric layer [12]; The function of displaying different colors in the visible light range is realized by changing the material characteristics and the geometric parameters 2 of 9 of the structure, in order to achieve the application of the structure color [13][14][15][16][17][18][19]. However, the devices proposed by researchers have the defects of single function, complex structure and expensive materials; they cannot achieve better performance when the devices are integrated.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the TE‐polarized light demonstrated in Figure b, the transmission bandwidths are much wider with different peak transmission characteristics, which make their corresponding colors different from those of TM‐polarized light. Therefore, a single pixel filled with proposed metasurface produces variable transmitted colors in perpendicular planes, showing distinctive color characteristics compared to temperature‐modulated dynamic color generation …”
mentioning
confidence: 99%